In Search of Mobile Applications for Patients With Pelvic Floor Disorders. Issue 9 (September 2019) - Sudol, Neha T.; Adams-Piper, Emily; Perry, Rachel; Lane, Felicia; Chen, Katherine T.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2019;25: 252–256) Multiple medical societies have issued guidelines emphasizing the importance of patient education, behavioral therapy, and/or exercise regimens in the initial treatment and management of women with pelvic floor disorders. Even with these well-established recommendations, however, it is often difficult to engage patients and maintain adherence to treatment plans.